2021
DOI: 10.3138/jvme-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

Video Recording in Veterinary Medicine OSCEs: Feasibility and Inter-rater Agreement between Live Performance Examiners and Video Recording Reviewing Examiners

Abstract: The Objective Structured Clinical Examination (OSCE) is a valid, reliable assessment of veterinary students’ clinical skills that requires significant examiner training and scoring time. This article seeks to investigate the utility of implementing video recording by scoring OSCEs in real-time using live examiners, and afterwards using video examiners from within and outside the learners’ home institution. Using checklists, learners (n=33) were assessed by one live examiner and five video examiners on three OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Raters in this study reported they spent a considerable amount of time rating the videos and welcomed the prescribed break after rating four recordings. Similar findings were reported by Tan et al (2020) in a study evaluating rating of digitally recorded OSCE stations 65 . Digitally recorded evaluations of surgical skills have also been assessed for evidence of reliability in other veterinary studies, 20,23,26,52,66 so this remains a feasible option.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Raters in this study reported they spent a considerable amount of time rating the videos and welcomed the prescribed break after rating four recordings. Similar findings were reported by Tan et al (2020) in a study evaluating rating of digitally recorded OSCE stations 65 . Digitally recorded evaluations of surgical skills have also been assessed for evidence of reliability in other veterinary studies, 20,23,26,52,66 so this remains a feasible option.…”
Section: Discussionsupporting
confidence: 70%
“…Similar findings were reported by Tan et al (2020) in a study evaluating rating of digitally recorded OSCE stations. 65 Digitally recorded evaluations of surgical skills have also been assessed for evidence of reliability in other veterinary studies, 20,23,26,52,66 so this remains a feasible option. While the digital recordings in this study were used solely to collect data for the reliability study, digital recordings can be a powerful tool to provide feedback to students on their performance to help them enhance their proficiency and will be considered for this purpose in the future.…”
Section: Discussionmentioning
confidence: 99%
“…64 To date, the OSCE been widely used in veterinary education, including the evaluation of surgical skills, sometimes mixed with nonsurgical clinical skills. [65][66][67][68] Objective structured clinical examinations are multistation, multirater assessments where the student rotates between stations and raters, being scored on discrete tasks rather than entire procedures. 69 Reliability of an OSCE is dependent upon having an adequate number of stations, rater training if multiple raters are used to score the same station, and good-quality rubrics.…”
Section: Forms Of Surgical Assessmentmentioning
confidence: 99%
“…While in-person scoring of OSCE and surgical performance typically allows the best visualization of the trainee performing the task, having raters score video recorded OSCE stations has proven feasible and reliable, although it did not reduce the time required for grading and there were some differences between examiners in pass/fail decisions at individual stations. 67 Scoring other surgical skills examinations using video recordings has also generated reliable results. 78,86 GoPro video cameras have been used, either head mounted 95 or attached to a surgical light, 86,96 to capture surgical videos successfully.…”
Section: Video Recorded Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation